Development of Academic Expectations of Pre-Service Teacher Professional Education (PPG) Students - Harum, Akhmad; Anas, Muhammad; Latif, Suciani; Samad, Sulaiman; Bakhtiar, Muh Ilham (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2023)
The purpose of this study was to determine the development of academic expectations of pre-service teacher professional education (PPG) students. The method used in this research is a qualitative method with a type of case study research. The research subjects were determined through a purposive sampling technique conducted on 8 pre-service PPG students in the field of Guidance and Counseling studies in 2023. Data collection techniques used observation techniques, in-depth interviews, and journal writing at the beginning of the semester and the end of the semester through Google Forms. Data analysis techniques are used with conventional models in the form of thematic analysis techniques. The results showed that the development of academic expectations of Pre-service PPG students has changed over time. The influencing factors are college experience, academic achievement, social support, and greater self-expectations to achieve academic goals. Academic expectations vary between students from different backgrounds, such as family education level, economic status, or previous experience in education. Academic expectations have an impact on how students plan their careers after graduating from the Pre-Service PPG